Kidney disease and congenital heart disease: Partnership for life - El Sayegh, Skye; Ephrem, Georges; Wish, Jay B.; Moe, Sharon; Lim, Kenneth (Frontiers in Physiology, 2022)
The literature on the relationship between kidney and cardiovascular diseases is continuously expanding. Scientists have elucidated many of the neurohormonal and hemodynamic pathways involved in cardiorenal disease. However, little is known about kidney disease in patients with congenital heart disease. Given advances in the medical and surgical care of this highly complex patient population, survival rates have dramatically improved leading to a higher percentage of adults living with congenital heart disease. Accordingly, a noticeable increase in the prevalence of kidney disease is appreciated in these patients. Some of the main risk factors for developing chronic kidney disease in the adult congenital heart disease population include chronic hypoxia, neurohormonal derangements, intraglomerular hemodynamic changes, prior cardiac surgeries from minimally invasive to open heart surgeries with ischemia, and nephrotoxins. Unfortunately, data regarding the prevalence, pathophysiology, and prognosis of chronic kidney disease in the adult congenital heart disease population remain scarce. This has led to a lack of clear recommendations for evaluating and managing kidney disease in these patients. In this review, we discuss contemporary data on kidney disease in adults with congenital heart disease in addition to some of the gaps in knowledge we face. The article highlights the delicate interaction between disease of the heart and kidneys in these patients, and offers the practitioner tools to more effectively manage this vulnerable population.